2020
DOI: 10.5696/2156-9614-10.28.201207
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Modelling for River Activities Management: Example from a Low- and Middle-Income Country

Abstract: Background. Rivers are susceptible to pollution and water pollution is a growing problem in low- and middle-income countries (LMIC) with rapid development and minimal environmental protections. There are universal pollutant threshold values, but they are not directly linked to river activities such as sand mining and aquaculture. Water quality modelling can support assessments of river pollution and provide information on this important environmental issue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…To some extent, a water quality model is an important evaluation index and forecasting tool for water pollution, and is important for people's lives. In 2020, Izni Zahidi et al [47] established the water quality model for river activity management in Malaysia. It is an important research which revealed the trends in pollutants in this area over the years and the percentage of time each pollutant exceeded a certain category.…”
Section: Mine Groundwater Quality Modelingmentioning
confidence: 99%
“…To some extent, a water quality model is an important evaluation index and forecasting tool for water pollution, and is important for people's lives. In 2020, Izni Zahidi et al [47] established the water quality model for river activity management in Malaysia. It is an important research which revealed the trends in pollutants in this area over the years and the percentage of time each pollutant exceeded a certain category.…”
Section: Mine Groundwater Quality Modelingmentioning
confidence: 99%
“…Water hyacinth has choked it, causing floods and silting. Mudslides often result due to environmental deterioration brought about by bush burning and agricultural practices in the River Rwizi’s upstream catchment zones [ 11 ]. The increase in population in Mbarara city has resulted into poor sanitation practices amidst low toilet coverage and substandard solid waste disposal management [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tis is because they are important freshwater sources; however, it is the most susceptible to pollution. Moreover, good water quality is essential because it plays a major role in supporting life, food production, energy generation, industry, and environmental support capacities including domestic consumption, agriculture, transportation, tourism, and other required water activities [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the source of pollution entering the Cikeas River (West Java) was dominated by housing complexes and the Celeungsi River (West Java) was dominated by industrial sector while the Bekasi River (Wes Java) was dominated by shopping centers, hotels, and restaurants [4]. Tis condition is also widespread in countries with low and middle incomes such as Indonesia, Malaysia, and Myanmar where rapid developments are followed with minimal environmental considerations [2]. Furthermore, the examples of dominant stressors in the lotic system (80% of all water bodies) include hydromorphology degradation, point resource pollution distribution, and water use [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation